Biology of Parrotfishes - Hoey, Andrew S.; Bonaldo, Roberta M.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Parrotfish are found on almost every coral reef in the world. This ubiquity and uniqueness of their feeding action make them one of the most important groups of fishes within coral reef ecosystems. But why, exactly, are parrotfish soimportant to reefs? Can the evolution of a particular jaw morphology and feeding action really have had such a large impact on the health and functioning of the world's coral reefs? This book introduces the reader to this fascinating group of fishes (Labridae, Scarinae), from the morphological innovation of a jaw that has the power to bite through solid calcium carbonate, to the threats currently faced by parrotfish populations around the world. It contains new insights into their diet and food processing ability, and lifehistories, and concludes with an overview of emerging and future research directions.
Evolution. Evolution of the Parrotfishes: A Highly Modified Wrasse or Unique Family? Speciation and Biogeography of the Parrotfishes. Morphological Specialization of the Parrotfishes. Functional Diversity and Innovation Within the Skull of Parrotfishes. Biology. Nutritional Ecology of Parrotfishes. Age, Growth and Longevity of Parrotfishes. Reproduction of Parrotfishes. Vision and Color Patterns in Parrotfishes. Ecology. Linking Form to Function: the Unique Role of Parrotfishes on Coral Reefs. Functional Ecology of Parrotfishes: the Influence of Species, Size, and Temperature. Functional Variation Among Parrotfishes: Are They Complementary or Redundant? Bioerosion and Sediment Production. the Good, the Bad, and the Ugly: Parrotfishes as Coral Predators. Geographic Variation in the Composition and Function of Parrotfishes. Seasonal Dynamics of Algae and Parrotfish Grazing. the Role of Parrotfishes on Marginal Reef Systems. the Ecology of Parrotfishes on Low Coral Cover Reefs. Spatial Ecology of Parrotfishes. Fisheries and Conservation. Traditional Fisheries and the Conservation and Management of Parrotfishes. Marine Protected Areas, Trophic Cascades and Parrotfish Grazing on Caribbean Reefs. Marine Protected Areas, Trophic Cascades and Parrotfish Grazing on Indo-Pacific Reefs. Changes in Biodiversity and Functioning of Parrotfish Assemblages Following Disturbance. the Biology and Ecology of Parrotfishes: Emerging Topics and Future Directions.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Life Sciences / Evolution; SCIENCE / Life Sciences / Biology / Marine Biology; Parrotfishes; Electronic books